Group Activity Therapy Stretching as Preventive Action for Musculoskeletal Emergencies in the Elderly at Healthcare and Rehabilitation Unit Magetan - Hery Ernawati; Sri Andayani; Elfa Afiani; Nur Alvi; Apdha Triwulan Hafsarini; Retno Dwi Ambarwari (Universitas STRADA Indonesia, 2025)
Aging impacts musculoskeletal function declines, such as joint stiffness and muscle pain, which can trigger geriatric emergencies like falls and immobilization. This study aimed to determine the effectiveness of stretching-based group activity therapy in reducing pain and improving mortality in the elderly. The design used was a quasi-experimental pre-test and post-test without a control group, involving 47 elderly at the Pelayanan Sosial Tresna Werdha Magetan (Healthcare and Rehabilitation Unit). The intervention was conducted in one 40-minute, consisting of statistical and dynamic stretching of several body parts. Evaluation was conducted using a Visual Analog Scale. Results showed a significant reduction in pain (median Visual Analog Scale from 6–8 to 2–3) and active participation by all participants. The discussion confirmed that group activity therapy stretching is effective as a non-pharmacological intervention for preventing chronic pain and the risk of musculoskeletal emergencies in the elderly, and provides psychosocial benefits through group interaction.